PENGARUH PEMBERIAN PUPUK ORGANIK CAIR NIAS TERHADAP PRODUKSI TANAMAN SAWI MANIS (Brassica juncea L.) - Yawazaro Telaumbanua; Armaini Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The mustard sweet (Brassica juncea L) is much appreciated consumer especially organiced organic.  One of the organic materials that have potential to be applied is POC Nias, but not yet known the right concentration to obtain maximum production.Research on POC Nias is done with the aim of determining the best concentration in increasing the growth and production of mustard plants. The study was conducted in Desa Muda Setia, Bandar Sei Kijang Sub-district from March to April 2018, using a randomized block design method (RAK) 6 treatment with 5 replications. The treated treatment is without fertilization, fertilized with 2g Urea + 1g KCl per plant, POC Nias concentration 5ml-1, 10ml-1, 15ml-1, 20ml-1). The observed parameters of plant height, number of leaves, leaf area, fresh weight, root volume, fresh weight are feasible for consumption. The results showed that POC Nias can increase the growth and production of sweet mustard plants with the best concentration is 10 ml-1 water.Keywords: mustard sweet, liquid organic fertilizer Nias, concentration, production